Pengaruh modifikasi perilaku extinction terhadap perilaku kecanduan pornografi - Sarif, Nur Ikhsan Mahmudi (Maliki Interdisciplinary Journal, 2024)
Individuals who are entering the adolescent phase are individuals who are full of curiosity, want to try everything even though it is not good. In this phase, teenagers are familiar with the outside world, which they have never met. Most teenagers are not yet able to control themselves and express their existence consistently. This condition is caused by many factors such as environment, intelligence, relationships and knowledge. For this reason, behavior modification is used as a strategy to overcome deviant behavior in adolescents. There are many methods, approaches, concepts and techniques that can be used in behavior modification. Extinction is also a strategy to stop reinforcing inappropriate or inappropriate behavior. This is because many behaviors do not last long due to positive reinforcement for the behavior. This study aims to determine the effect of a behavior modification program to reduce door slamming and throwing things when angry with the elimination method. This study uses the case study method with a single subject, so that the effects of the modifications that have been given can be properly evaluated. The data collection methods used in this research are observation and experiment. The subject in this study consisted of one person, aged 19 years, and had a bad habit, namely the desire to watch porn videos excessively. The results of this study indicate that a behavior modification program with the method of elimination (extinction) to reduce the subject's behavior can be said to be successful. Changes in the frequency of watching pornographic videos have decreased quite significantly. This is due to the awareness and desire of the subject to return to normal so that the subject succeeds in modifying behavior.